Effect of Tax Avoidance, Profitability, Leverage on Cost of Debt with Institutional Ownership as Moderating - Brigita Wahyu Yuliarti; Nuramalia Hasanah; Tri Hesti Utamaningtyas; Etty Gurendrawati; Unggul Purwohedi (AIBPM Publisher, 2021)
The purpose of this study is to determine and also examine the effect of tax avoidance, profitability, leverage on the cost of debt with institutional ownership as moderating agent in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The sampling method used is purposive sampling with 22 listed companies included in the sampling criteria. The data is obtained from financial reports downloaded from the company's own website or the IDX. The analytical method used is moderate regression using SPSS 25. The results of this study indicate that tax avoidance has a positive and insignificant effect on the cost of debt. Profitability has a negative and significant effect on the cost of debt. And leverage has a negative and significant effect on the cost of debt. Then, institutional ownership is not able to moderate the effect of tax avoidance on the cost of debt. Meanwhile, institutional ownership is able to moderate the effect of profitability and leverage on the cost of debt.